2018
DOI: 10.3389/fmicb.2018.01631
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Is Associated With Reduced Morbidity and Mortality in Porcine Circovirus Associated Disease

Abstract: Porcine circovirus associated disease (PCVAD) is a term used to describe the multi-factorial disease syndromes caused by porcine circovirus type 2 (PCV-2), which can be reproduced in an experimental setting through the co-infection of pigs with PCV-2 and porcine reproductive and respiratory syndrome virus (PRRSV). The resulting PCVAD-affected pigs represent a subpopulation within the co-infected group. In co-infection studies, the presence of increased microbiome diversity is linked to a reduction in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Control of Campylobacter infections in poultry remain challenging and, to date, no methods for effective control at the farm level have been developed, other than the application of stringent biosecurity. Previous literature has demonstrated that the intestinal microbiota can play a role in resistance to enteric pathogens in mice (16), chickens (14; 19) and pigs (36). Consequently, we investigated the contribution of caecal microbiota to the differential resistance of inbred chicken lines 6 1 and N to colonization by C. jejuni, which have been demonstrated by experimental inoculation with several C. jejuni strains (6; 7).…”
Section: Discussionmentioning
confidence: 99%
“…Control of Campylobacter infections in poultry remain challenging and, to date, no methods for effective control at the farm level have been developed, other than the application of stringent biosecurity. Previous literature has demonstrated that the intestinal microbiota can play a role in resistance to enteric pathogens in mice (16), chickens (14; 19) and pigs (36). Consequently, we investigated the contribution of caecal microbiota to the differential resistance of inbred chicken lines 6 1 and N to colonization by C. jejuni, which have been demonstrated by experimental inoculation with several C. jejuni strains (6; 7).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is also very common among piglets (Song et al, 2015). Fecal microbiota transplantation (FMT) has been shown to be effective in lowering the risk of diarrhea in piglets (Bin et al, 2018;Niederwerder et al, 2018). The mechanisms by which FMT decreases diarrhea in piglets remain to be determined, but they are probably multifaceted, such as enhanced beneficial microbes, increased microbiome diversity, and restored normal microbiota (Niederwerder, 2018) and maintenance of gut barrier functions (Cheng et al, 2018;Geng et al, 2018).…”
Section: Repeated Inoculation With Rumen Microbiota Reduces Diarrheamentioning
confidence: 99%
“…The microbiota within the gastrointestinal tract has been demonstrated to be involved in nutrient metabolism and immune system development and function, and disruptions of the microbiota cause long-term health problems [10]. Some of these problems include necrotising enterocolitis, a reduced immune response following infection and an associated higher susceptibility to disease, reduced growth and diarrhoea in pigs [11][12][13][14]. As such, the development or maintenance of a healthy gut microbiota is important for health and survival.…”
Section: Introductionmentioning
confidence: 99%